2016
DOI: 10.1002/slct.201600300
|View full text |Cite
|
Sign up to set email alerts
|

Guest‐Induced, Self‐Assembled Supramolecular Capsule: Effect of Guest and Counter Anions

Abstract: Molecular capsules form due to various interactions between molecules. Cyclotricatechylene (CTC) is a poly‐phenolic macrocycle that has been shown to form capsule under highly basic conditions. Here, we describe the formation of a molecular capsule under ambient conditions, from CTC by addition of a guest molecule. The capsule is most probably forming through pure electrostatic interaction between the guest and CTC. The capsule formation has been studied using solution techniques such as NMR and Mass spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The hydroxy groups of CTC are potential hydrogen-bonding groups, and dimeric CTC capsules form in solution and solid state through a self-assembly templated by binding NEt 4 + cations within the capsule. 16 Earlier reports showed that dimeric hydrogen-bonded capsules of partially deprotonated CTC can be isolated in the solid state with encapsulated NEt 4 + guests. These capsules were not entirely closed and had a clam-shell like appearance (Figure 1).…”
mentioning
confidence: 99%
“…The hydroxy groups of CTC are potential hydrogen-bonding groups, and dimeric CTC capsules form in solution and solid state through a self-assembly templated by binding NEt 4 + cations within the capsule. 16 Earlier reports showed that dimeric hydrogen-bonded capsules of partially deprotonated CTC can be isolated in the solid state with encapsulated NEt 4 + guests. These capsules were not entirely closed and had a clam-shell like appearance (Figure 1).…”
mentioning
confidence: 99%